Peran Influencer Media Sosial dan Herd Behavior Terhadap Keputusan Pembelian Produk Fashion Pada Mahasiswa Universitas Bangka Belitung - Maulana, Muhammad Yusuf; Herlianto, Danil; Putri, Dea Nazila; Veren, Veren; Putra, Agung Rizky (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2025)
The rapid development of social media has transformed consumer behaviour, particularly among younger generations in their purchasing decisions regarding fashion products. This study aims to explore the role of social media influencers in shaping consumer herd behaviour, and how these factors influence purchasing decisions among students at the University of Bangka Belitung. Employing a qualitative descriptive approach, primary data were collected through closed-ended questionnaires distributed to students who are active social media users and have experience in purchasing fashion products. The findings indicate that influencers contribute to creating positive perceptions of products through visual content and engaging personal narratives, while herd behaviour emerges from the tendency to follow trends and collective decisions within one's social environment. Students often make purchasing decisions not solely based on personal need but as a response to social pressure and a desire to stay relevant with prevailing trends. This research highlights the significance of understanding social dynamics in digital spaces to develop more context-sensitive and relevant marketing strategies for younger consumers. Abstrak Perkembangan media sosial telah mendorong perubahan perilaku konsumsi di kalangan generasi muda, termasuk dalam keputusan pembelian produk fashion. Penelitian ini bertujuan untuk memahami peran influencer media sosial dalam membentuk herd behavior konsumen serta bagaimana kedua faktor tersebut memengaruhi keputusan pembelian mahasiswa Universitas Bangka Belitung. Menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui penyebaran kuesioner tertutup kepada mahasiswa yang aktif menggunakan media sosial dan memiliki pengalaman melakukan pembelian produk fashion. Temuan menunjukkan bahwa influencer berkontribusi dalam menciptakan persepsi positif terhadap produk melalui konten visual dan narasi personal yang menarik, sedangkan herd behavior muncul dari kecenderungan mengikuti tren dan keputusan kolektif lingkungan sosial. Mahasiswa cenderung melakukan pembelian bukan semata-mata atas dasar kebutuhan, melainkan dorongan sosial dan keinginan untuk tidak tertinggal tren. Penelitian ini menyoroti pentingnya memahami dinamika sosial dalam ranah digital untuk menyusun strategi pemasaran yang lebih kontekstual dan relevan bagi konsumen muda